Characterization of ion channels on subesophageal ganglion neurons from Chinese tarantula Ornithoctonus huwena: Exploring the myth of the spider insensitive to its venom. (15th September 2016) - Deng, Meichun; Hu, Zhaotun; Cai, Tianfu; Liu, Kai; Wu, Wenfang; Luo, Xuan; Jiang, Liping; Wang, Meichi; Yang, Jing; Xiao, Yucheng; Liang, Songping
Abstract: Chinese tarantula Ornithoctonus huwena is one of the most venomous spiders distributing in the hilly areas of southern China. In this study, using whole-cell patch-clamp technique we investigated electrophysiological and pharmacological properties of ion channels from tarantula subesophageal ganglion neurons. It was found that the neurons express multiple kinds of ion channels at least including voltage-gated calcium channels, TTX-sensitive sodium channels and two types of potassium channels. They exhibit pharmacological properties similar to mammalian subtypes. Spider calcium channels were sensitive to ω-conotoxin GVIA and diltiazem, two well-known inhibitors of mammalian neuronal high-voltage-activated (HVA) subtypes. 4-Aminopyridine and tetraethylammonium could inhibit spider outward transient and delayed-rectifier potassium channels, respectively. Huwentoxin-I and huwentoxin-IV are two abundant toxic components in the venom of Ornithoctonus huwena . Interestingly, although in our previous work they inhibit HVA calcium channels and TTX-sensitive sodium channels from mammalian sensory neurons, respectively, they fail to affect the subtypes from spider neurons. Moreover, the crude venom has no effect on delayed-rectifier potassium channels and only slightly reduces transient outward potassium channels with an IC50 value of ∼51.3 mg/L. Therefore, our findings provide important evidence for ion channels from spiders having an evolution as self-defense and prey mechanism. Highlights: Tarantula neurons express at least voltage-gated calcium channels, TTX-sensitive sodium channels, and potassium channels. The tarantula ion channels exhibit pharmacological properties similar to mammalian subtypes. The findings provide important evidence for ion channels from spiders having an evolution as self-defense and prey mechanism.